Dento-legal issues in Malaysia : a general guide for dental practitioners - Haniwarda Yaakob (Penerbit Universiti Kebangsaan Malaysia, 2022)
Dentistry is a noble profession where dentists often manage to bring smiles and create confidence in patients. Nonetheless, as with other medical professionals, dentists too often encounter legal suits brought against them by their patients. Legal actions against dentists are not new in Malaysia, where several actions have been litigated in court. The rise in legal actions against medical professionals including dentists is associated with the increased awareness of patient’s rights and autonomy. Legal actions can cause several repercussions on dentists such as loss of reputation, shame and anxiety. As such, it is imperative for dentists to have the basic legal knowledge on the potential legal liability that they may face should something go wrong during the course of dental treatment. This is the main crux of this paper where several dento-legal cases that have been reported in Malaysian law journals are identified and analysed. This is followed with a brief discussion on the legal issues surrounding those cases. Legal principles governing the issues identified are provided in brief so as to provide dentists with basic legal knowledge on the legal aspect of dentistry.